Cowboy, cross my heart - Grant, Donna (Grant, Donna. Heart of Texas., 2018)
Naomi Pierce isn<U+2019>t the type to let a cowboy sweep her off feet. It<U+2019>s not her first rodeo, after all. But when she returns to her Texas hometown, she can<U+2019>t help but be swept up again in the rough-and-tumble world of hard-riding, bronco-busting good-ol<U+2019>-boys she loved as a girl. She might be here to photograph her Rodeo Queen best friend. But it<U+2019>s one fine-looking cowboy who really captures her eye<U+2026> Brice Harper is all man, all muscle, and all heart. From the moment he rides into the stadium, he can<U+2019>t help but notice the beautiful stranger with a camera watching him from the stands. It doesn<U+2019>t take a zoom lens to see the sparks of instant attraction. But things really heat up when he meets Naomi up-close<U+2015>and he discovers that someone is stalking her friend. Brice wouldn<U+2019>t be any kind of cowboy if he didn<U+2019>t offer to help the ladies out. But can the rough rider keep this spirited shutterbug out of danger<U+2015>without risking his heart?